2014
DOI: 10.1021/es502025e
|View full text |Cite
|
Sign up to set email alerts
|

Photoreduction and Stabilization Capability of Molecular Weight Fractionated Natural Organic Matter in Transformation of Silver Ion to Metallic Nanoparticle

Abstract: Photoinduced reduction of silver ion (Ag + ) to silver nanoparticles (AgNPs) by dissolved organic matter (DOM) plays a crucial role in the transformation and transport of engineered AgNPs and Ag + in aquatic environments. DOM is a mixture of natural polymers with wide molecular weight (MW) distribution, and the roles of specific components of DOM in the photoreduction of Ag + to AgNPs are still not understood. In this study, MW fractionated natural organic matter (M f -NOM) were investigated for their roles on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
58
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 84 publications
(64 citation statements)
references
References 57 publications
6
58
0
Order By: Relevance
“…The MW distribution, UV−vis spectroscopy and fluorescence excitation−emission spectroscopy of M f -NOMs prepared by ultrafiltration was characterized in our previous study. 20 Generally, the molar absorptivity at 280 nm increased with the increasing of MW, indicating the abundances of aromatic moiety in higher MW M f -NOMs. In addition, the maximum intensity of fluorescence peaks (in the range of 350/ 452−370/468 nm) increased as the MW of M f -NOM decreased, suggesting the abundances of carboxylic moiety in lower MW M f -NOMs.…”
Section: ■ Results and Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The MW distribution, UV−vis spectroscopy and fluorescence excitation−emission spectroscopy of M f -NOMs prepared by ultrafiltration was characterized in our previous study. 20 Generally, the molar absorptivity at 280 nm increased with the increasing of MW, indicating the abundances of aromatic moiety in higher MW M f -NOMs. In addition, the maximum intensity of fluorescence peaks (in the range of 350/ 452−370/468 nm) increased as the MW of M f -NOM decreased, suggesting the abundances of carboxylic moiety in lower MW M f -NOMs.…”
Section: ■ Results and Discussionmentioning
confidence: 90%
“…19 In our previous study, we observed that high MW Suwannee River NOM plays more significant role in stabilizing NOM-reduced AgNPs in the presence of Ca 2+ than low MW NOM. 20 These findings further highlighted the importance of the distinguishing roles of different NOM fractions in the transport and subsequent chemical transformation and toxicity of engineered AgNPs. However, in commercial AgNPs products, AgNPs are often modified with various capping agents or coatings, which make the interaction between AgNPs and NOM more complicated.…”
Section: ■ Introductionmentioning
confidence: 92%
“…In addition, as DOM is a mixture with wide molecular weight (MW) distribution, the exact roles of specific components of DOM in the photoreduction of Ag + to AgNPs are still not well understood. In a recent study [28], we found that the difference of MW fractionated natural organic matter (M f -NOM) on photoreduction of Ag + was mainly ascribed to the differential light attenuation of M f -NOM, rather than the "real" reductive ability. More importantly, compared with low MW fractions, high MW M f -NOMs showed drastically higher capability in stabilizing the photosynthesized AgNPs against Ca 2+ -induced aggregation.…”
Section: /Fementioning
confidence: 98%
“…This red-shift was also observed for AgNPs in the presence of Cu 2+ , which should be ascribed to the divalent metal ion-induced aggregation and fusion of AgNPs. 32,33 Then, SOD, a specific superoxide scavenger, 34,35 was added to the growing cultures to further validate the role of superoxide in AgNP formation. Figure 3B shows that SOD can partially abolish the formation of AgNPs by F. oxysporum, demonstrating the critical role of superoxide in the reduction of silver.…”
Section: Environmental Science and Technology Lettersmentioning
confidence: 99%
“…The different peak shape of spectra indicated the different sizes or aggregation states of AgNPs, 33 which may be associated with the experimental batchdependent composition and concentration of extracellular polymeric substances that play an important role in stabilizing AgNPs. 36 Activity of Enzymes Responsible for Superoxide Production.…”
Section: Environmental Science and Technology Lettersmentioning
confidence: 99%